DNA Curtains for High-Throughput Single-Molecule Optical Imaging - Greene, Eric C. (Methods Enzymol, 2010)
Single-molecule approaches provide a valuable tool in the arsenal of the modern biologist, and new discoveries continue to be made possible through the use of these state-of-the-art technologies. However, it can be inherently difficult to obtain statistically relevant data from experimental approaches specifically designed to probe individual reactions. This problem is compounded with more complex biochemical reactions, heterogeneous systems, and/or reactions requiring the use of long DNA substrates. Here we give an overview of a technology developed in our laboratory, which relies upon simple micro- or nanofabricated structures in combination with “bio-friendly” lipid bilayers, to align thousands of long DNA molecules into defined patterns on the surface of a microfluidic sample chamber. We call these “DNA curtains,” and we have developed several different versions varying in complexity and DNA substrate configuration, which are designed to meet different experimental needs. This novel approach to single-molecule imaging provides a powerful experimental platform that offers the potential for concurrent observation of hundreds or even thousands of protein–DNA interactions in real time.